Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Di Toko Batik Benang Raja Kota Semarang - Hermawan Budiyanto (Universitas 17 Agustus 1945 Semarang, 2022)
Product quality is a key factor in influencing consumer satisfaction. The study is aimed at investigating and analyzing the impact of product quality on consumer satisfaction levels in the clothing industry. The study uses survey and interview methods to collect data from 54 responden involved in the purchase of products at King's Wire Shops in Semarang. Data analysis results show that product quality has a significant positive impact on customer satisfaction. Therefore, this research provides valuable insights for companies in their efforts to improve consumer satisfaction through improved product quality.